The impact of trauma exposure and moral injury on UK military veterans: a qualitative study. Issue 1 (31st December 2020) - Williamson, Victoria; Murphy, Dominic; Stevelink, Sharon A. M.; Allen, Shannon; Jones, Edgar; Greenberg, Neil
ABSTRACT: Background : Exposure to a potentially morally injurious event (PMIE) has been found to be associated with a range of adverse mental health outcomes. However, how the psychological consequences following PMIEs compare to those encountered after a traumatic, but not a PMIE, remain poorly understood. Objective : The aim was to qualitatively explore UK military veterans' responses to experiences of trauma and moral injury and the impact of such events on psychological wellbeing. Method : Thirty male veterans who reported exposure to traumatic and/or morally injurious events were recruited. Semi-structured qualitative interviews were conducted, and data were analysed using thematic analysis. Results : Six veterans described exposure to a non-morally injurious traumatic event, 15 reported experiencing a PMIE, and 9 described exposure to a 'mixed' event which was simultaneously morally injurious and traumatic. Veterans who encountered a PMIE described experiencing moral dissonance, or a clash between concurrently held sets of values (e.g. military values versus civilian values), which provoked considerable psychological distress. Veterans' cognitions and responses were found to differ following a PMIE compared to a traumatic, but not PMIE, which could have negative implications for daily functioning. Several risk and protective factors for experiencing distress following a PMIE were described. Conclusions : This study provides some of the first evidence that events experienced by UK veterans can simultaneously be morally injurious and traumatic or life-threatening as well as highlighting the process by which moral injury may occur in UK veterans. These findings illustrate the need to examine effective pathways for prevention and intervention for veterans who have experienced a morally injurious event.